PENGARUH PERILAKU PROSOSIAL TERHADAP KECEMASAN KEMATIAN YANG DIMODERASI RASA SYUKUR PADA LANSIA DI KOTA BANDUNG - Afina Zahirah, - (2019)
This study aims to determine the effect of prosocial behavior on death anxiety moderated by gratitude of the elderly in Bandung. This research used a quantitative approach with a correlational method. The sample in this study were 405 elderly lived in Bandung. The sampling technique in this study used incidental sampling. The instruments used in this study were: prososcialness scale from Caprara et al. (2005), GQ-6 created by McCullough, Emmons, and Tsang in 2002 and has been adapted by Dienillah (2017), and Death Anxiety Scale (DAS) by Templer in 1970 and has been adapted by Huriyah (2016). Data were analyzed with linear regression analysis to determine the effect of prosocial on death anxiety and multiple regression to determine the effect of prosocial on death anxiety moderated by gratitude. The results showed that gratitude increases the effect of prosocial behavior on death anxiety in the elderly in Bandung. Keywords: Death Anxiety, Elderly, Gratitude, Prosocial Behavior.